Mutation Analysis of H3F3A and H3F3B as a Diagnostic Tool for Giant Cell Tumor of Bone and Chondroblastoma. (November 2015) - Cleven, Arjen H.G.; Höcker, Saskia; Briaire-de Bruijn, Inge; Szuhai, Karoly; Cleton-Jansen, Anne-Marie; Bovée, Judith V.M.G.
Abstract : Specific H3F3A driver mutations and IDH2 mutations were recently described in giant cell tumor of bone (GCTB) and H3F3B driver mutations in chondroblastoma; these may be helpful as a diagnostic tool for giant cell–containing tumors of the bone. Using Sanger sequencing, we determined the frequency of H3F3A, H3F3B, IDH1, and IDH2 mutations in GCTBs (n=60), chondroblastomas (n=12), and other giant cell–containing tumors (n=24), including aneurysmal bone cyst, chondromyxoid fibroma, and telangiectatic osteosarcoma. To find an easy applicable marker for H3F3A mutation status, H3K36 trimethylation and ATRX expression were correlated with H3F3A mutations. In total, 69% of all GCTBs harbored an H3F3A (G34W/V) mutation compared with 0% of all other giant cell–containing tumors ( P <0.001), whereas 70% of chondroblastomas showed an H3F3B (K36M) mutation compared with 0% of other giant cell–containing tumors ( P <0.001). Diffuse H3K36 trimethylation positivity was more often seen in mutated H3F3A GCTBs compared with other giant cell–containing tumors ( P =0.005). ATRX protein expression was not correlated with H3F3A mutation status. Hotspot mutations in IDH1 or IDH2 were absent. Our results show that H3F3A and H3F3B mutation analysis appears to be a highly specific, although less sensitive, diagnostic tool for the distinction of GCTB and chondroblastoma from other giant cell–containing tumors. Although H3K36 trimethylation and ATRX immunohistochemistry cannot be used as surrogate markers for H3F3A mutation status, mutations in H3F3A are associated with increased H3K36 trimethylation, suggesting that methylation at this residue may play a role in the etiology of the disease. Abstract : Supplemental Digital Content is available in the text.